Motor Competence in Autistic Children with Attention-Deficit Hyperactivity Disorder - Jadiane Dionisio; Cristina dos Santos Cardoso de Sá; Susana Lúcio; Gabriela Neves de Almeida; Rita Cordovil (Children)
Background/Objectives: Children with autism exhibit deficits in fundamental motor skills, which are intensified when associated with attention-deficit/hyperactivity disorder (ADHD). Objective: To correlate motor competence in children with autism, autism levels according to the CARS scale, and the association with ADHD. Methods: This cross-sectional study assessed motor competence using the Motor Competence Assessment (MCA), the severity of Autism Spectrum Disorder by Childhood Autism Rating Scale (CARS), and the presence of clinical signs for ADHD using Swanson, Nolan, and Pelham (SNAP-IV) questionnaire. A total of 68 children were recruited; however, 23 were not included due to non-acceptance and/or were excluded because of associated pathologies, high autism severity. Consequently, 45 children (11 with ADHD) between the ages of 5 and 11 (Mean: 8.15; ±1.75) with 83.72% being male. Results: Multiple linear regression revealed a significant inverse correlation between MCA scores and raw CARS data (p = 0.01), indicating that greater autism severity is associated with lower motor competence. The correlation was also observed in CARS classifications, with higher autism severity corresponding to lower motor percentiles (p = 0.05). However, the correlation between the presence of ADHD and motor competence in children with ASD did not reach significance. Overall, a significant correlation was observed (p = 0.006) when analyzing all variables (CARS scores, SNAP scores, and CARS classification). Conclusion: Therefore, it is believed that children with autism exhibit deficits in functional motor skills, with severity impacting motor competence. The findings underscore the need for systematic motor skill assessments in children with autism, emphasizing the importance of monitoring and intervention in this aspect of their development.